DOES RENEWABLE ENERGY REDUCE ESG RISK? EVIDENCE FROM ENERGY-INTENSIVE INDONESIAN FIRMS (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2026)
The main objective is to determine whether renewable energy adoption effectively reduces ESG risk and whether this effect varies depending on the level of energy intensity. Using a purposive sample of 180 firm-year observations from companies included in the ESG Leader Index during 2021–2023, the research applies fixed-effect regression analysis, supplemented by robustness tests that classify firms into low and high energy intensity groups. The findings indicate that companies adopting renewable energy experience significantly lower ESG risk compared to those that do not, with the effect being more pronounced in energy-intensive industries. In addition, the role of independent commissioners is shown to strengthen ESG risk reduction in high energy intensity firms, while institutional ownership has no significant impact. These results confirm stakeholder theory, legitimacy theory, and risk management theory, as renewable energy adoption simultaneously enhances stakeholder trust, secures social legitimacy, and mitigates sustainability-related risks. The novelty of this study lies in providing empirical evidence from an emerging market and in emphasizing the moderating role of energy intensity. JEL: G32, Q42, Q56.